AN APPROACH OF DOM RECORD MANAGEMENT COMPONENT UI CREATION: AN APPROACH OF DOM RECORD MANAGEMENT COMPONENT UI CREATION - Atanasov, Valentin (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2024)
This paper presents an approach of Document Object Model database record management component user interface (UI) creation. Mainstream of UI development approaches concentrates in few directions, omitting holistic view on the fundamental database operations. The proposed solution uses method lay on of standard clauses adopted by the ECMA Script edition sixth and above. The program logic for the UI component was built with the intention - The existing functionality of such UI component to be extended and complemented.